2008
DOI: 10.1242/jcs.030056
|View full text |Cite
|
Sign up to set email alerts
|

The GPI-anchored superoxide dismutase SodC is essential for regulating basal Ras activity and for chemotaxis of Dictyostelium discoideum

Abstract: A genetic screen for Dictyostelium mutant displaying high level of constitutive phosphatidylinositol (3,4,5)-trisphosphate led to the finding that the glycosylphosphatidylinositol (GPI)-anchored superoxide dismutase SodC regulates small GTPase Ras. Cells that lack SodC exhibited constitutively high levels of active Ras, more membrane localization of GFP-PHcrac, and defects in chemoattractant sensing, cell polarization and motility. These defects of SodC-lacking cells were partially restored by expression of wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Considering that SodC is regulating RasG, which in turn controls PI3K activation and thus macropinocytosis, the aberrant hyperactivation of RasG in sodC -cells is likely the cause for the decreased particle uptake. It is, however, puzzling that PI3K inhibition did not improve particle uptake of sodC -cells, considering that LY294002 treated sodC -cells displayed excellent chemotaxis (Veeranki et al, 2008). It is thus likely that there exist additional defects that hamper particle uptake behavior of This study, for the first time, demonstrated that proper metabolism of reactive oxygen species Superoxide is critical for efficient particle uptake, proper trafficking of the internalized particles, and exocytosis in Dictyostelium cells.…”
Section: Sodc -Cells Are Defective In Exocytosismentioning
confidence: 79%
See 3 more Smart Citations
“…Considering that SodC is regulating RasG, which in turn controls PI3K activation and thus macropinocytosis, the aberrant hyperactivation of RasG in sodC -cells is likely the cause for the decreased particle uptake. It is, however, puzzling that PI3K inhibition did not improve particle uptake of sodC -cells, considering that LY294002 treated sodC -cells displayed excellent chemotaxis (Veeranki et al, 2008). It is thus likely that there exist additional defects that hamper particle uptake behavior of This study, for the first time, demonstrated that proper metabolism of reactive oxygen species Superoxide is critical for efficient particle uptake, proper trafficking of the internalized particles, and exocytosis in Dictyostelium cells.…”
Section: Sodc -Cells Are Defective In Exocytosismentioning
confidence: 79%
“…Cells that lack Superoxide Dismutase C, experience oxidative stress as a result of modestly increased intracellular superoxide level (~18% higher compared to wild type), high basal RasG activity and defects in chemoattractant sensing, cell polarization and motility (Veeranki et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, GTP bound Ras proteins were purified from cells lysates using pulldown assays as previously described by Veeranki, S. et al 2008. The activated forms of RasD and RasG were purified using recombinant GST-Ras binding domain (RBD) from mammalian Raf1 (GST-RBDRaf1) and the activated form of RasC was purified using recombinant GST-Ras Binding Domain of Byr2 from Schizosaccharomyces pombe (GST-RBDByr2).…”
Section: Determining Ras Activation In Response To Camp Stimulationmentioning
confidence: 99%